PEMBELAJARAN KITAB TA’LIM AL-MUTA’ALIM UPAYA INTERNALISASI NILAI-NILAI KARAKTER - Yuliana Yuliana (Al Fattah Ejournal Sma Al Muhammad Cepu, 2023)
Good educational results are characterized by outputs that lead to the realization of morality, and the formation of character in real life. This study uses a descriptive qualitative approach, aimed at describing, and analyzing the planning, implementation, and internationalization model of character values in MTs Miftakhul Huda Bojonegoro. The results of this study are as follows: (1) In planning including; a) material, b) objectives, c) learning methods, and d) analysis of needs in learning. (2) The process of internalizing character values through the study of the book of Ta'lim Al-Mut'allim uses three stages: 1) Transformation of values. At this stage, the focus is on understanding the material value in the book of Ta'lim Al-Mut'allim. 2) Value transactions, This stage occurs two-way mutual interaction between students and teachers actively. 3) The stage of trans-internalization of the character. In this stage, the teacher and students begin to correlate between the character values that are in the book of Ta'lim Al-Mut'allim, which can be carried out in real life